sin(x+y)cosx+cos(x+y)sinx=1/3 x∈(3π/2,2π) 求cos(2x+π/4)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 16:37:51
sin(x+y)cosx+cos(x+y)sinx=1/3x∈(3π/2,2π)求cos(2x+π/4)sin(x+y)cosx+cos(x+y)sinx=1/3x∈(3π/2,2π)求cos(2x+
sin(x+y)cosx+cos(x+y)sinx=1/3 x∈(3π/2,2π) 求cos(2x+π/4)
sin(x+y)cosx+cos(x+y)sinx=1/3 x∈(3π/2,2π) 求cos(2x+π/4)
sin(x+y)cosx+cos(x+y)sinx=1/3 x∈(3π/2,2π) 求cos(2x+π/4)
x∈(3π/2,2π)所以2x∈(3π,4π) 原式=SIN(2X+Y)=1/3 即2X+Y在3/派下,或在2派/3下方且在X轴上方
原式=SIN(2X+Y)=1/3 则COS(2X+Y)=
cos(2x+π/4)=(1/根号2)*COS2X+(1/根号2)*SIN2X
化简sin(x+y)sinx+cos(x+y)cosx
化简sin(x+y)sinx+cos(x+y)cosx等于?
化简cos(x+y)sinx-sin(x+y)cosx
化简cos(x+y)sinx-sin(x+y)cosx
sinx*sin(x+y)+cosx*cos(x+y)等于?
cos(x+y)sinx-sin(x+y)cosx
y= sin x cos x+sinx+cosx的值域
Y= SIN X - COS X / 2 COSX 的导数Y= SIN X - COS X / 2 COSX 的导数
cos(x+y)*cos(x-y)=cos*cosx+sin*siny
cos(x+y)-cosx如何等于-2sin[(2x+y)/2]sin(y/2),
证明sinx+cos(x+y)siny/cosx-sin(x+y)siny=tan(x+y)
证明cosx-cos(x+2y)/2siny= sin(x+y)证明cosX-cos(x+2y)/2siny= sin(x+y)
为什么y=sinx,y=-sin(-x)=sinx,y=cosx,y=-cos(-x)=-cosx
请问怎么证明sinX+sin(X+Y)+sin(X+2Y)/cosX+cos(X+Y)+cos(X+2Y)=tan(X+Y),
求y=|cosx| y=|tanx| y=sin|x| y=cos|x| y=tan|x|周期
已知sin(x-y)cosx-cos(x-y)sinx=3/5求tan2y的值
若cos(x+y)cosy+sin(x+y)siny=0,则cosx=
已知Sin(x+y)Cosx-Cos(x-x)Sinx=3/5求tan2y的值